PERBANDINGAN KADAR TRIGLISERIDA PADA OBES 1 DAN OBES 2 - Oway, Inri A. H.; Kalangi, Sonny J. R.; Pasiak, Taufik (Universitas Sam Ratulangi, 2013)
Abstract. Background. Triglycerides are a type of fat that can be found in blood which are stored the most in human body. Triglycerides are used as an energy source for various metabolic processes. High levels of triglycerides can lead to various health problems. Elevated triglycerides levels can be caused by various things, such as obesity. Obesity results when fat accumulates in body. Obesity and elevated triglycerides levels can affect human health. Objective. The aim for this research was to compare triglyceride levels of obese 1 and obese 2 students of Faculty of Medicine Sam Ratulangi University. Method. An observational method with cross sectional design research was done to compare triglyceride levels in obese 1 and obese 2 students of Faculty of Medicine Sam Ratulangi University Â academic year 2010 and 2011. In the number of 49 people, (30 people were obese 1 and 19 people were obese 2). The data were analyzed using SPSS, test of hypothesis used Mann Whitney. Â Result. The mean values of triglyceride levels in obese 1 students were 69,00 mg/dL and in obese 2 students were 85,53 mg/dL. Conclusion. There were significant differences on triglyceride levels in obese 1 and obese 2. Keyword: fat, obesity, triglyceride. Â Abstrak. Latar Belakang. Trigliserida merupakan jenis lemak yang paling banyak pada tubuh manusia dan dapat ditemukan dalam darah. Trigliserida berguna sebagai sumber energi untuk berbagai proses metabolik tubuh. Akan tetapi jika kadar trigliserida terlalu tinggi maka dapat menimbulkan berbagai masalah kesehatan. Peningkatan kadar trigliserida dapat disebabkan oleh berbagai hal, salah satunya karena obesitas. Obesitas terjadi karena peningkatan akumulasi lemak dalam tubuh. Obesitas dan peningkatan kadar trigliserida dapat mempengaruhi tingkat kesehatan seseorang. Tujuan. Penelitian ini bertujuan untuk membandingkan kadar trigliserida pada mahasiswa obes 1 dan obes 2 Angkatan 2010 dan 2011 di Fakultas Kedokteran Universitas Sam Ratulangi. Metode. Penelitian ini dilakukan dengan metode observasional dan desain studi cross sectional untuk membandingkan kadar trigliserida pada mahasiswa obes 1 dan obes 2 Angkatan 2010 dan 2011 di Fakultas Kedokteran Universitas Sam Ratulangi. Jumlah sampel pada penelitian ini sebanyak 49 orang yang terdiri dari 30 orang obes 1 dan 19 orang obes 2. Analisis data dilakukan dengan menggunakan SPSS dan uji hipotesis menggunakan Uji Mann-Whitney. Hasil. Kadar trigliserida rata-rata pada obes 1 sebesar 69,00 mg/dL dan kadar trigliserida rata-rata pada obes 2 sebesar 85,53 mg/dL. Kesimpulan. Secara statistik terdapat perbedaan bermakna kadar trigliserida pada obes 1 dan obes 2. Kata Kunci: lemak, obesitas, trigliserida.